The Storytelling Method Using Finger Shadow Puppets to Improve Sentence Construction Skills in Early Childhood - Hasanah, Uswatun; Hasan, Aliah Bagus Purwakania; Zirmansyah, Zirmansyah (CV. Publikasi Indonesia, 2026)
This research aims to improve the ability to compose sentences in early childhood through the application of the storytelling method using finger puppet media. The focus of the research is directed toward the development of children's expressive language skills, especially in composing simple sentences that are sequential, meaningful, and contextually appropriate to the story. This study uses a Classroom Action Research (PTK) approach carried out in an early childhood institution with group B children as research subjects. The population in this study consists of all group B children, with a research sample of 10 children determined using a saturated sampling technique. The data analysis technique was conducted descriptively, qualitatively, and quantitatively by comparing the improvement in children's abilities in each action cycle. The results of the study show a significant increase in children's sentence-composing skills after the application of the storytelling method using puppets. Children became more active, confident in speaking, able to compose sentences with more complete structures, and showed great enthusiasm during storytelling activities. Improvements were observed in each cycle, both in terms of vocabulary, fluency in speaking, and the ability to tell stories coherently. Based on these findings, it can be concluded that the storytelling method using finger puppet media is effective in improving the ability to compose sentences in early childhood. Therefore, it is recommended that PAUD teachers use wayang jari media as an alternative for creative and innovative learning.